Application Design Of Heavy Equipment Maintenance In PT Bumi Borneo Perkasa - Rosmana, Rio Sonja; Sudarmaningtyas, Pantjawati; Hariyani, Sri (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT Bumi Borneo Perkasa (BBP) is a mining contractors company. process of mining needs help of heavy equipment. PT BBP has heavy equipment about 150 units. in Condition, the heavy equipment of PT Bumi Perkasa Burneo often damaged because it was late in the replacement of spare parts, and delayed in obtaining a license for heavy equipment, and no reports for maintenance costs of each heavy equipment.The solution the above problems is designing and building maintenance applications of heavy equipment at PT BBP using SDLC method With the first stage is communication, planning, construction modeling. The results based from the application trials, maintenance applications of heavy equipment has been made can solve the problem in the division of heavy equipment. This Application generate alert of replacement spare parts by regularly, give an alert to renew permits heavy equipment and provide maintenance cost reports of each Heavy equipment. maintenance applications of heavy equipment save the data of heavy equipment, spare parts and heavy equipment license.